Pink lemonade cake murder - Fluke, Joanne, 1943- (Fluke, Joanne, 1943- Hannah Swensen mystery, 2023)
The Tri-County Summer Solstice Celebration has come to town, and even among local artisans, athletes, and marching bands, Hannah attracts fans of her own while serving lip-smacking pink lemonade desserts. But the mood sours when a body turns up, leading revelers to wonder if the festivities mark both the longest day of the year and the deadliest. A retired professional MLB player has met a terrifying end and, considering the rumors swirling about his past, the list of suspects could fill a small stadium. Among them could soon be Delores, Hannah s mother, who publicly held a grunge against the victim after he infamously dunked her in the tank at a previous county fair. Now, with her mother's innocence on the line, a life-changing announcement at The Cookie Jar, and a plethora of desserts to bake, Hannah can't afford to strike out as she begins a dangerous investigation into the ruthless killer who's truly in a league of their own.